Fungal infections from the diabetic foot ulcers in AL-Samawah city - Akeel Hamed Al-Oebady, Mouna (Al-Qadisiyah Journal of Pure Science, 2018)
A total of 150 samples from diabetic foot ulcers at many ages for both genders (86 male and 64 female) were collected from patients suffering from diabetic wounds infections who attending the Samawah Hospital of AL-Muthanna province during the period from June 2015 to May 2016. The fungal infections of diabetic foot were caused by Candida species. Candida albicans was the most common causative agent 46\103( 44.66%) , followed by C. tropicalis, C. dublinensis, C. krusei, C.parapsilosis and C. guillermondi were 23 (22.33%), 15(14.56%), 9(8.73%), 6(5.82%) and 4(3.88%) respectively. The highest incidence was Aspergillus spp 23\47 (48.93%) . The other molds isolated were Penicillium marneffei 14(29.78 %), Fusarium solani 8 (17.02 %), and Basidiobolus ranarum 2 (4.25 %).